High prevalence of long COVID in anti-TPO positive euthyroid individuals with strongly elevated SARS-CoV-2-specific T cell responses and moderately raised anti-spike IgG levels 23 months post-infection - Matula, Zsolt; Király, Viktória; Bekő, Gabriella; Gönczi, Márton; Zóka, András; Steinhauser, Róbert; Uher, Ferenc; Vályi-Nagy, István (Frontiers in Immunology, 2024)
Severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) infection, the causative agent of coronavirus disease 2019 , causes post-acute infection syndrome in a surprisingly large number of cases worldwide. This condition, also known as long COVID or post-acute sequelae of COVID-19, is characterized by extremely complex symptoms and pathology. There is a growing consensus that this condition is a consequence of virus-induced immune activation and the inflammatory cascade, with its prolonged duration caused by a persistent virus reservoir. In this cross-sectional study, we analyzed the SARS-CoV-2-specific T cell response against the spike, nucleocapsid, and membrane proteins, as well as the levels of spike-specific IgG antibodies in 51 healthcare workers, categorized into long COVID or convalescent control groups based on the presence or absence of post-acute symptoms. Additionally, we compared the levels of autoantibodies previously identified during acute or critical COVID-19, including anti-dsDNA, anti-cardiolipin, anti-β2-glycoprotein I, anti-neutrophil cytoplasmic antibodies, and anti-thyroid peroxidase (anti-TPO). Furthermore, we analyzed the antibody levels targeting six nuclear antigens within the ENA-6 S panel, as positivity for certain anti-nuclear antibodies has recently been shown to associate not only with acute COVID-19 but also with long COVID. Finally, we examined the frequency of diabetes in both groups. Our investigations were conducted at an average of 18.2 months (convalescent control group) and 23.1 months (long COVID group) after confirmed acute COVID-19 infection, and an average of 21 months after booster vaccination. Our results showed significant differences between the two groups regarding the occurrence of acute infection relative to administering the individual vaccine doses, the frequency of acute symptoms, and the T cell response against all structural SARS-CoV-2 proteins. A statistical association was observed between the incidence of long COVID symptoms and highly elevated anti-TPO antibodies based on Pearson's chi-squared test. Although patients with long COVID showed moderately elevated anti-SARS-CoV-2 spike IgG serum antibody levels compared to control participants, and further differences were found regarding the positivity for anti-nuclear antibodies, anti-dsDNA, as well as serum TSH and HbA1c levels between the two groups, these differences were not statistically significant.